STRUCTURES OF ENGLISH VOCABULARY IN USE - Pulatova Durdona Turgun kizi; Feruza Kucharova Alisher kizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
A dictionary is an essential tool for language learners, offering meanings, pronunciations, and examples of words in use. It provides the foundation for understanding and using new vocabulary effectively. Dictionaries come in various formats, such as print, online, or as mobile applications, making them accessible to everyone. Using a dictionary requires knowing its structure. Words are typically arranged alphabetically, with additional information like word types (noun, verb, adjective, etc.), definitions, synonyms, antonyms, and example sentences. Many dictionaries also include phonetic transcriptions, which help with proper pronunciation. To use a dictionary effectively, you should first identify the word you want to look up and locate it using the alphabetical order. Once found, pay attention to the word’s meaning, grammatical use, and context.